Primary Health Care Technicians in the learning processes - Cabanilla S. , Denyi Fabiola; Elizalde C. , Cecilia Isabel; Cepeda A., Katuska (Revista Minerva, 2023)
Sign language is a language that meets all the linguistic processes necessary for communication, however, there is no great interest in learning it. The objective of creating a guide with teaching activities for the inclusive teaching of sign language in children from 4 to 5 years old, so that students of regular education know a new way of communicating and become sensitized to the deaf community. The activities provide the opportunity to acquire a vocabulary according to the educational level in which the proposal is applied, in turn, signal language is promoted and the awareness of a deaf community that before the law has the right and duties but that are not yet one hundred percent respected. The methodological design was qualitative-quantitative, through a bibliographic, field, exploratory, descriptive research and the application of surveys, interviews, checklist with which valuable information was collected after tabulating and analyzing them ... and analyzing them, the conclusions and recommendations were established in which the benefits of learning sign language as a communicative process stand out, the beneficiaries were the teachers and students so that in the future there is a true social inclusion.
Keywords: Teaching activities; inclusive teaching; sign language; didactic guide